Formation shape transition of multiple mobile robots in leader-follower method - Fujimori, Atsushi; Oh-kiri, Kotaro; Oh-hara, Shinsuke (IAES International Journal of Robotics and Automation (IJRA), 2021)
This paper presents a formation shape transition technique of multiple mobile robots in the leader-follower method as a new function that gives flexibility to the formation control of mobile robots with multiple sonars. First, we propose basic shape transition methods for the case of two mobile robots under formation control by the leader-fol lower method, and then extend the methods to the shape transition of three mobile robots. Since the multiple sonars attached to the mobile robot are located forward, including the left and right sides, there is a constraint on the formation shape feasible by the leader-follower method. In the case of two mobile robots, the follower must be positioned behind the leader. Therefore, there are three shapes of the follower relative to the leader: line, right-back, left-back. In the case of three mobile robots, t hree types of line, zigzag, triangle shapes are considered. The effectiveness of the proposed technique is demonstrated by experiments using real mobile robots.